Implementasi Program Penanganan Nelayan Pelintas Batas Negara di Wilayah Kerja Stasiun Psdkp Belawan - Sunaryo Sunaryo; Arifiani Widjayanti; Hamka (Syntax Corporation, 2023)
Fishermen who cross national borders are an important issue in marine and fisheries development, especially in border areas. To deal with this problem, Minister of Marine and Fisheries Affairs Regulation Number 39/PERMEN-KP/2016 has been stipulated. This research focuses on answering the implementation of the Minister's regulations located at Belawan Marine and Fisheries Surveillance Station, North Sumatra which is not yet optimal, with a descriptive qualitative approach. Data collection techniques were carried out using interviews, observation and document review. Researcher used purposive sampling techniques to determine informants. The result of the research is that all aspects of the policy implementation model from Van Meter and Van Horn have not been achieved as a measure of the success of implementing Ministerial Decree Number 39/PERMEN-KP/2016, which is due to the fact that policy standards and objectives have not been fully able to resolve problems, limited budged, and the economic, social and political external environment. The recommendations given include revising Marine and Fisheries Ministerial Regulation Number 39/PERMEN-KP/2016, providing assistance with facilities and infrastructure for cross national border fishermen, providing early education to fishermen's children, increasing the budget, synergizing surveillance operations at sea between the Ministry of Marine Affairs and Fisheries, Indonesian Republic Police, Indonesian Navy to prevent the occurrence of fishermen crossing state borders, built an integrated location at the location of fishermen crossing borders with the Modern Fisherman's Village model.